PLASMA MODIFICATION OF MICROFIBERS - APPLICATION TO LIGHTWEIGHT CEMENT COMPOSITE CONTAINING RECYCLED CONCRETE - Jakub Ďureje; Zdeněk Prošek; Jan Trejbal; Pavel Tesárek; Štěpán Potocký (Acta Polytechnica CTU Proceedings)
The article deals with the optimalization of composition for reinforced lightweight cement composite containing micronized recycled concrete, which will be used to produce masonry blocks. The composite material is reinforced with polypropylene microfibers. To increase the cohesion between the fibers and the cementitious matrix, the optimal modification using oxygen plasma was chosen. Furthermore, a suitable foaming agent was chosen to lighten the cement matrix. A suitable ratio of cement and micronized recycled concrete was determined. Finally, a cement composite was made from the optimized components. The mechanical properties of this composite were tested. The resulting mechanical properties of the lightweight samples were compared with the non-light samples.